Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2174/1381612823666170210150147
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt Pathway: A Potential Therapeutic Target for Chronic Pain

Abstract: Chronic pain is among the most disabling and costly disorders, with prevalence ranging from 10% to 55%. However, current therapeutic strategies for chronic pain are unsatisfactory due to our poor understanding of its mechanisms. Thus, novel therapeutic targets need to be found in order to improve these patients' quality of life. PI3K and its downstream Akt are widely expressed in the spinal cord, particularly in the laminae I-IV of the dorsal horn, where nociceptive C and Aδ fibers of primary afferents princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 129 publications
6
48
0
Order By: Relevance
“…Although the pAKT pathway typically regulates cell growth and survival, increasing evidence indicates the involvement of this pathway in the development and maintenance of chronic pain [27,28]. Our data further showed that pAKT was predominantly expressed in DRG neurons after CFA injection.…”
Section: A and B)supporting
confidence: 72%
“…Although the pAKT pathway typically regulates cell growth and survival, increasing evidence indicates the involvement of this pathway in the development and maintenance of chronic pain [27,28]. Our data further showed that pAKT was predominantly expressed in DRG neurons after CFA injection.…”
Section: A and B)supporting
confidence: 72%
“…In animal model of DPN, PI3K/AKT pathways were repressed and then the expression of neurogenesis-related factors was downregulated [36]. Besides, activation of PI3K/AKT pathway has promise in the management of DPN, as it is capable of controlling chronic pain [37]. Other than PI3K/AKT pathway, b-catenin pathway has been mentioned to be critical in DPN.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research has suggested that numerous extracellular signaling molecules and intracellular transduction pathways are involved in chronic pain. 21 24 The Janus family tyrosine kinase (JAK)/signal transducers and activators of transcription (STAT) pathway is one of the most important cell signaling pathways in chronic pain, which includes four types of JAK and seven types of STAT. 25 , 26 Our previous study has demonstrated that STAT1 contributes to CIBP by regulating MHC II expression in spinal microglia.…”
Section: Introductionmentioning
confidence: 99%